PERBANDINGAN METODE CERAMAH DENGAN METODE DEMONSTRASI PADA PENGUKURAN LILA TERHADAP HASIL BELAJAR - Adriani, Adriani; Darmawati, Junay; Fransisca, Lidya (Jurnal Kesehatan Abdurrahman, 2025)
ABSTRACT Pregnant women with Chronic Energy Deficiency (KEK) are one of the determinants of the risk of nutritional and health problems in their babies. According to the results of the 2018 Riskesdas, in Indonesia there are 17.3% of pregnant women experiencing KEK, so early detection is necessary. As a midwife students, they are expected to be able to conduct an early screening for pregnant women with an accurate upper arm circumference (LILA) examination. The purpose of this study was to find out the best method between lectures and demonstrations in getting the best learning outcomes from LILA measurement skills in Diploma III Midwifery STIKES Al-Su'aibah students. This type of research is quasi-experimental research (Quasi-Experiment). The population of this study were 44 students of Diploma III Midwifery STIKES Al-Su'aibah. The research variables include the independent variables, namely the lecture method and the demonstration method, while the dependent variable is the learning outcomes from LILA measurements. The results showed that the average student learning outcomes using the lecture method was 75.95 which was smaller than the average student learning outcomes using the demonstration method, namely 85.29. Statistical test results obtained p value = 0.016 < α 0.05, which means that there is a significant difference in average student learning outcomes between the lecture method and the demonstration method so that the hypothesis stating that there is a difference between the lecture method and the demonstration method is statistically proven. It is hoped that this research can help facilitate learning so that it is better to use the demonstration method so that learning objectives can be achieved.Keywords: lecture, demonstration, measurement of upper arm circumference